The uranium age in Portugal and Spain (1947-1980) - Madureira, Nuno Luis; Bartollomé. Isabel (XIX World Economic History Congress, 2022)
Despite Portugal and Spain sharing environmental commonalities and political affinities between their dictatorships were more than clear at the dawn of the atomic business, the responses turned out significantly different. Portugal dismissed nuclearization after several endeavors whilst ten atomic reactors were connected up to the Spanish national grid in 1985. Hence, if similar conditions produce different results, the devil must be in the details. This paper attempt to cast light on the devil. To this end, we present a more fine-grained analysis of the circumstances surrounding the nuclear history of both nations, highlighting particularly three new variables: business structure; economic policy and political actors; and access to capital. Notwithstanding the statistical register of affinities, we conclude that nuclear power hit an Iberian world endowed with different business capacities, different energy policies and different actors in motion.